Analisis Yuridis Terhadap Prilaku Wanprestasi Sopir Angkutan Umum Terhadap Penumpang - Muzammil (JOURNAL SAINS STUDENT RESEARCH, 2023)
The existence of a development in Transportation Technology has had a positive impact, namely providing convenience in the mobility of a country's population in carrying out an activity. The progress of transportation is an indication that a country has a developing economy, this is because transportation is the lifeblood of a country's economic development. Nowadays, the development of transportation technology continues to experience very rapid development and it is impossible to predict when it will end. Indonesia is Indonesia's largest archipelagic country with an area of ​​9.8 million KM2 and a population of 237,556,363 million in 2010, according to the Indonesian Central Statistics Agency. Due to its vast territory and large population, it is very common for the mobility that occurs in Indonesia to be very large. Given this fact, the existence of transportation that has supporting qualities is very important. Transportation that has a quality that supports it is not just talking about the quality of its transportation performance. But also the services provided by related agencies or parties also include the services of transport drivers who are the actors closest to consumers or passengers, where there are not many transport drivers, especially public transport, who often commit acts of default by breaking an agreement with passengers regarding fares. or costs, passenger stopping places and so on. This research is normative research. Researchers who study through existing regulations and are library materials.